ANALISIS AKTIVITAS BELAJAR SISWA PADA MATA PELAJARAN IPA KELAS V DI SDN DURI KEPA 05 DALAM MASA PANDEMI COVID-19 - Reza Novayulianti; Harlinda Syofyan (Jurnal Inovasi Penelitian, 2021)
This study aims to understand a student's learning activity in the fifth grade science subject at SDN Duri Kepa 05 during the Covid-19 pandemic. As well as to find out learning activities brave (in the network), learning activities, inhibiting factors, advantages and disadvantages, how to overcome problems so that it runs well. This form of research uses a descriptive approach. Sources of data used in this study are primary data sources and secondary data. The data collection procedure was carried out by means of observation, interviews, and documentation. The results show that for the form of bold learning activities given by the teacher, namely giving assignments using Zoom Meetings and delivering material through video media in WhatsApp Groups. Furthermore, learning activities use virtual applications, namely Zoom Meetings, radio stations, TVRI broadcasts, and WhatsApp applications, and applications for assigned tasks. The inhibiting factor is cellphone, internet quota. The personal obstacles that parents feel are that it is difficult to wake their children, and the lessons are difficult for parents to understand. The advantages and disadvantages of bold learning in science learning are that the advantages are still not said more because science adds more material through practice and simulations that require touch. The drawback is that the process of delivering material to students is still lacking. And for how to overcome it in science learning so that learning activities are carried out well, namely through videos, explaining via Zoom, simplifying the practicum and experiment processes